E-Cefit Test (Certification Test) sebagai Penunjang Profesi Akuntan dalam Menghadapi Era Artificial Intelligence - Esmawati, Esmawati; Fitriyaningsih, Fitriyaningsih; Narulitasari, Devi (Jurusan Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Pekalongan, 2021)
Technology is increasingly developing into a means to facilitate human work and activities. One of them facilitates the performance of an accountant to be able to complete work precisely, quickly, and accurately. The sophistication of this technology is the main target so that every job can be completed perfectly with the help of the application system. Technological sophistication that can be utilized in the accounting field, especially by an accountant, is in the form of using an application system that utilizes artificial technology. But on the other hand, it is feared that technological developments will eventually be able to shift the accounting profession itself. To become a professional accountant, of course, requires certification that has met the qualification standards in accordance with the main competencies and special competencies in the accounting field. This study seeks to improve the soft skills of accountants to be able to compete in the artificial intelligence era so that the accounting profession cannot be replaced in the future. The implementation of this soft skill improvement is in the form of special training based on application technology, which is able to support the performance and readiness of accountants in facing the Certified Statement of Financial Accounting Standards or often abbreviated as CPSAK. This study uses a descriptive qualitative approach as an effort to understand the various concepts found in the research process, using content analysis techniques. Content analysis technique is a research method used to find out the conclusions of a text or in other words, content analysis is a research method that wants to reveal the author's ideas that want to be implemented. From this research, it is able to produce the application of E-Cefit Test (Certification Test) as a special training effort in order to be able to produce professional accountants. This application is designed to prepare prospective accountants to pass the certification exam through technology-based online learning media.